2015
DOI: 10.5194/hessd-12-12947-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of road and railway embankments on runoff and soil erosion in eastern Spain

Abstract: Abstract. Road and railway infrastructure increased in the Mediterranean region during the last three decades. This included the building of embankments, which are assumed to be a~large source of sediments and runoff. However, little is known about soil erosion rates, the factors that control them, and the processes that contribute to detachment, transport and deposition of sediments from road and railway embankments. The objective of this study was therefore to assess the impacts of road and railway embankmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 108 publications
(82 reference statements)
0
23
0
1
Order By: Relevance
“…In total sixty rainfall simulation experiments were carried out at 55 mm h −1 rainfall intensity for one hour on circular paired plots of 0.25 m 2 . The intensity chosen for this experiment represents a high intensity, low frequency storm as occurs in the Mediterranean climate prevailing in this area with a return period of 10 years (Castillo and Beltran, 1977;Pereira et al, 2015). The experimental trial took place in July 2013, when soil moisture was the lowest of the year.…”
Section: Field Experiments and Laboratory Analysesmentioning
confidence: 99%
“…In total sixty rainfall simulation experiments were carried out at 55 mm h −1 rainfall intensity for one hour on circular paired plots of 0.25 m 2 . The intensity chosen for this experiment represents a high intensity, low frequency storm as occurs in the Mediterranean climate prevailing in this area with a return period of 10 years (Castillo and Beltran, 1977;Pereira et al, 2015). The experimental trial took place in July 2013, when soil moisture was the lowest of the year.…”
Section: Field Experiments and Laboratory Analysesmentioning
confidence: 99%
“…Estimated soil loss amounts in slopes were significantly different (p<0.001) from each other and were about 4.940 t/ha/yr in cut slope, 2.191 t/ha/yr in fill slope, and 0.717 t/ ha/yr in control slope, respectively (Table 3). In a study in Spain, average soil loss amount in a road route of an open area was measured as 3.0 t/ha/yr [26]. We found that soil loss in cut slope was approximately 2.5 times higher than fill slope.…”
Section: Changing Soil Loss and Other Soil Properties Depending On Romentioning
confidence: 72%
“…In the absence of robust soil and water conservation, the challenges of soil erosion increase, leading to soil detachment and increased run-off on soil surface [4,8,12]. Land form changes owing to infrastructure development in form of roads, often create new landscape factors which change soil properties from the additional drainage culverts in road and other infrastructural projects [13]. This new development increases both on-site and off-site disturbances of the ecosystems.…”
Section: Introductionmentioning
confidence: 99%